A Study of the Association between Drug Abuse and Duration of Exclusive Breastfeeding in Mothers in Sabzevar City, Iran - Roghieh Javan; Ahmad Delbari; Yaser Tabaraei; Masoumeh Hashemian; Hoda Ahmari Tehran (Majallah-i Dānishgāh-i ̒Ulūm-i Pizishkī-i Qum, 2014)
Background and Objectives: Today, drug abuse is one of the major health problems that put many population groups, such as mothers and their newborns, at serious risk. This study aimed to determine the association between drug abuse and duration of exclusive breastfeeding in the mothers of Sabzevar city.